Mechanical properties and energy dissipation of rock under acid corrosion and coupled static-dynamic loads - Liu Yong-sheng; Li Jin; Zou Jia-yu; Wu Qin-lan; Liu Wang (Functional Materials, 2017)
The dynamic impact experiment were carried out to investigate the dynamic mechanical properties of different types of rocks under acidic environment and coupled static-dynamic loads. The experimental results showed that the mechanical properties of marble and red sandstone are affected by acid corrosion, impact pressure and coupled loading. Based on the principle of energy conservation and the experimental results, the energy dissipation law of the red sandstone under coupled static-dynamic loads was analyzed. The analysis results show that with the increasing of the impact pressure, the average strain rate increases, and the incident energy increases linearly, and the reflection energy and energy absorption show a slow growth trend; The transmission energy is almost unaffected by the impact pressure, and the fitting curve is approximate to a straight line. The results show that there is an obvious correlation between the dynamic strength of rock and the absorbed energy. The higher the impact pressure is, the greater the absorption energy is, the higher the strength of the rock under static and dynamic combination is.